Healthy neonates birthweight according to gestational age in a Lima population - Pacora, Percy (2005)
Objetive: To determine healthy neonates birthweight born from healthy Lima pregnant women without obstetrical complications. Materials and Methods: A retrospective, analytic and transversal study was conducted. Maternal and perinatal data was retrieved from the Department of Obstetrics/Gynecology and Pediatrics Database at Hospital Nacional Docente Madre-Niño San Bartolome from January 1, 1991 through December 31, 1999. Healthy singleton pregnant women 20 to 30 years old, BMI 20 to 25 kg/mt2 , without obstetrical complications, with a difference ± 2 weeks between last menstrual period and gestational age by physical assessment of the healthy living neonate were selected. Results: Birthweights of 5,443 healthy neonates in Lima [50th percentile [10th percentile- 90th percentile]) at 35, 36, 37, 38, 39, 40, 41, and 42 gestational weeks were 2640 (2346-3356), 2850 (2430- 3344), 3100 (2688-3632), 3200 (2770-3700), 3300 (2850- 3770), 3370 (2950-3850), 3450 (3030-3980) , 3512 (3102 – 4000) grams. Male healthy fetuses at term weighted 108 grams more than female fetuses (p<0,001). Conclusions: Fetal weight increases with gestational age. Fetuses born before 35 weeks are sick. Male healthy fetuses at term weighted 108 grams more than female fetuses on average. As compared with female fetuses, healthy male fetuses did not gain weight after 41 weeks.